PENGENDALIAN PERAMBAHAN HUTAN TNKS: RELOKASI PENDUDUK KERINCI TAHUN 1990 - Hanif Risa Mustafa; Dennys Pradita; Septi Utami (Universitas Sultan Ageng Tirtayasa, 2026)
The designation of Taman Nasional Kerinci Seblat (TNKS) as a conservation area in the mid-1980s raised new issues. This area was designated sterile to human activity, prohibiting residents from engaging in activities within it. However, illegal practices such as encroachment continue. Based on this, this study aims to examine efforts to save the TNKS area during the New Order era and their implications for the local community in the 1990s. This research uses historical methods. The primary sources used are contemporary newspapers. The results show that efforts to save the TNKS area were carried out through a policy of relocating residents to transmigration areas. This policy not only affected ecosystem protection but also had social consequences, including the marginalization of the local population, restrictions on access to resources, and changes in community lifestyles through the transmigration program.